An Analysis Of Code-Mixing Used By A Lecturer In English Class - Tsamratul’aeni; Rahmawati Upa (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This research aims to find out the types of code-mixing used by the lecturer in English class. This research used both Qualitative methods. The subject in this research is the lecturer and the first yearof science students at CokroaminotoPalopo University. The instruments of this research are observation sheet and recorder. The result of this research shows that there are three types of code-mixing found in the lecturer’s utterances during the English teaching-learning process. They are Intra sentential, intra lexical, and involve a change of pronunciation and the results showed that the most frequent is intra sentential.